1999
DOI: 10.1021/ja990449w
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Cobalt Ethylene Polymerization Catalysts Bearing 2,6-Bis(Imino)Pyridyl Ligands:  Synthesis, Structures, and Polymerization Studies

Abstract: The synthesis, characterization, and ethylene polymerization behavior of a series of iron and cobalt halide complexes, LMX n (M ) Fe, X ) Cl, n ) 2, 3, X ) Br, n ) 2; M ) Co, X ) Cl, n ) 2), bearing chelating 2,6-bis(imino)pyridyl ligands L [L ) 2,6-(ArNCR 1 ) 2 C 5 H 3 N] is reported. X-ray diffraction studies show the geometry at the metal centers to be either distorted square pyramidal or distorted trigonal bipyramidal. Treatment of the complexes LMX n with methylaluminoxane (MAO) leads to highly active eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

69
791
7
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,035 publications
(869 citation statements)
references
References 60 publications
69
791
7
2
Order By: Relevance
“…This result is consistent with that reported in the literature [14]. It is suggested that, for bulky catalysts larger amounts of MAO should be required.…”
Section: Influence Of Ratio [Al]/[fe]and Structure Of the Ligandssupporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with that reported in the literature [14]. It is suggested that, for bulky catalysts larger amounts of MAO should be required.…”
Section: Influence Of Ratio [Al]/[fe]and Structure Of the Ligandssupporting
confidence: 93%
“…After being stirred at 353 K for 15 min, the reaction was allowed to cool to room temperature. The obtained material was concentrated, and diethyl ether (30 ml) was added to precipitate the product as a blue powder, which was subsequently washed 3 times with diethyl ether (3x10 ml); after this, it was filtered and dried [14].…”
Section: Synthesis and Characterizations Of Iron(ii) Complexesmentioning
confidence: 99%
“…[29][30][31] Chain growth with these catalysts is believed to occur via a Cossee-type mechanism whereby k p ≈ k t . Experimental evidence for the involvement of this mechanism was initially obtained from C 2 H 4 /C 2 D 4 co-oligomerization experiments using a bis(imino)pyrdine cobalt(I) chloride catalyst similar to 3, in combination with MAO.…”
Section: Introductionmentioning
confidence: 99%
“…These chemicals were dehydrated by passing them through a MS-13X column and were degassed by bubbling N2 before use. The bis(imino)pyridine derivatives (PBI-1 and -2) were prepared by the condensation reaction of 2,6-diacetylpyridine and substituted aniline according to a procedure described in the literature 3) . Triethylaluminum (TEA), diethylaluminum chloride (DEAC), and triisobutylaluminum (TIBA) as aluminum compounds were purchased from Kanto Chemical Co., Inc. MAO was obtained from the Sigma-Aldrich Corp.…”
Section: Methodsmentioning
confidence: 99%